The family impact of childhood atopic dermatitis: Scoping review. (2018) - Yamaguchi, Chikae; Sasaki, Kumiko; Asano, Midori
Highlights: The attributes of this concept fall into both child and parent domains. The child domain is comprised of four categories and the parent domain, of five. The analysis encompasses the effects of the disease on the QoL of a family. Our results enable specialists with more comprehensive assessment of the families.